Analisa Hubungan Peran Ganda Wara Terhadap Stres Kerja Sebagai Pendidik dan Tenaga Kependidikan AAU Dalam Era Society 5.0 - Garnis Maulidya; Sauzan Arjusnana R; Sherly Aprilia Islami Putri; Gagat Riano; Ismoyo Ismoyo (Akademi Angkatan Udara, 2021)
When career women are not able to balance the two roles, they will experience a conflict known as dual role conflict. On this basis, it is necessary to analyze the relationship between Wara's dual role and work stress as educators and education personnel at the Air Force Academy as part of the readiness of the AAU's role to prepare Indonesian Air Force human resources in the era of society 5.0. The research method used in this study is a correlational quantitative method. The variables in this study are self-adjustment as the dependent variable and the dual role as the independent variable. Based on the research, it can be concluded that dual role conflict has a negative correlation with Wara AAU's work stress due to factors that can reduce work stress, namely setting a reasonable workload, task characteristics that are in accordance with Wara's nature as a woman, strong group cohesion and able to accommodate Wara's needs, as well as AAU's organizational structure and climate followed by leadership policies to provide relatively more flexible working hours, making it easier for Wara to manage carrying out her role as a housewife as well as a woman with a career.